2005
DOI: 10.1007/s11248-005-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Induced-Odour Emission of a Bt Maize and its Attractiveness to Parasitic Wasps

Abstract: The current discussion on the safety of transgenic crops includes their effects on beneficial insects, such as parasitoids and predators of pest insects. One important plant trait to consider in this context is the emission of volatiles in response to herbivory. Natural enemies use the odours that result from these emissions as cues to locate their herbivorous prey and any significant change in these plant-provided signals may disrupt their search efficiency. There is a need for practical and reliable methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 38 publications
2
56
0
Order By: Relevance
“…Similar findings have been reported elsewhere (Ngi-Song and Potting et al, 1997). Also, Cotesia marginiventris Cresson (Hymenoptera: Braconidae) and Microplitis rufiventris Kokujev (Hymenoptera: Braconidae), which are important larval parasitoids, were not able to distinguish between the odours of a Bt maize event and its near-isogenic line (Turlings et al, 2005). This indicates that growing Bt maize is not likely to affect host finding by stem borer larval parasitoids.…”
Section: Effect Of Bt Maize On the Ability Of Parasitoids To Locate Hsupporting
confidence: 88%
See 4 more Smart Citations
“…Similar findings have been reported elsewhere (Ngi-Song and Potting et al, 1997). Also, Cotesia marginiventris Cresson (Hymenoptera: Braconidae) and Microplitis rufiventris Kokujev (Hymenoptera: Braconidae), which are important larval parasitoids, were not able to distinguish between the odours of a Bt maize event and its near-isogenic line (Turlings et al, 2005). This indicates that growing Bt maize is not likely to affect host finding by stem borer larval parasitoids.…”
Section: Effect Of Bt Maize On the Ability Of Parasitoids To Locate Hsupporting
confidence: 88%
“…Obonyo (2009), however, showed that there were no significant differences in host acceptance ratio between Bt exposed and non-Bt reared larvae. Turlings et al (2005) observed that braconid parasitoids did not distinguish between odours of Bt and non-Bt maize plants in olfactometer experiments. Although a number of studies have found no significant differences in oviposition choice between hosts fed on transgenic and non-transgenic diets (Bell et al, 1999, Schoenmaker et al, 2001Schuler et al, 1999b), there are cases where parasitoids seem to distinguish by host quality (reviewed in Steidle and van Loon, 2003;Overholt et al, 1994;Sallam et al, 1999).…”
Section: Effect Of Bt Maize On Parasitoid Biologymentioning
confidence: 94%
See 3 more Smart Citations